Efforts to Resolve Psychological Conflict in the Novels Odd Even by Almira Bastari and Bad Girl in Pesantren by Intan Zahlia Sari - Widia Tamara; Karkono Karkono; Azizatuz Zahro (RIRAI Publisher, 2022)
This study aims to describe the efforts to resolve conflict in the novels Odd Even and Bad Girl in Pesantren. The method used is descriptive qualitative method with an objective approach. The data in this study are in the form of words, sentences, or paragraphs related to narratives, dialogues, and behaviors that indicate conflict resolution efforts. The data sources of this study are taken from the novels Odd Even and Bad Girl in Pesantren. The instrument used in data collection was the researcher herself who acted as the key instrument. The data collection technique in this study was carried out by reading and note-taking techniques with the work steps of reading intensively, careful and repeatedly the novel Odd Even and Bad Girl in Pesantren as a data search process that included conflict resolution efforts, marking data according to research problems and recording data. Data analysis techniques, researchers used the Milles & Huberman model by reducing data, presenting data and drawing conclusions. The results showed 39 data, consisting of 15 sublimation data, 10 rationalization data in the novel Odd Even, 7 sublimation data, 7 rationalization data in the Bad Girl in Pesantren novel. The conflict resolution efforts contained in the novel can be used as a reflection not to dissolve in sadness and direct ourselves towards positive things.